Albert the bear - Butterworth, Nick. ([New York] : HarperCollins, 2003)
The toys in Mr. Jolly's toy shop try to cheer up a sad-looking stuffed bear named Albert.
Originally published: Great Britain : HarperCollins, 2002.
Horn Book.
Kirkus Review.
3.8.
3.8
K-3
Keywords: Teddy bears -- Fiction; Toys -- Fiction; Teddy bears -- Fiction; Toys -- Fiction